Identification and Treatment of Elite Pencak Silat Athlete Injury: A Study of the Qualification Round of the PON XXI in 2023 - Rony Syaifullah; Haris Nugroho; Deny Pradana Saputro (Journal Of Sport Education (JOPE), 2024)
This study is important to find out the picture of injuries experienced by elite category pencak silat athletes and how to solve the injuries. The method used is a descriptive method with documentation study. The data collection technique uses secondary data, namely documentation data of pencak silat athletes who have injuries obtained from the medical team. Based on the pencak silat match at the Pra-Pon Solo elite championship held on September 11-13, 2023, and involving 681 athletes, only 12 male athletes were found to have injuries and all of them were in the competing category. This study provides general findings that the injuries that often occur in elite-level pencak silat matches are upper limb injuries (7 cases of injury). While the lower limbs were only found to have fewer injuries (4 cases of injury), and 1 case of fracture injury of unknown location. Regarding injury management, the different types of injuries that occur also have different follow-up treatments. Based on the findings, injuries to the head area, and injuries diagnosed with fractures or dislocations, some cases were treated additionally by sending athletes to the hospital for further action. In contrast, some others were first given drug treatment. Based on these findings, it can be concluded that injuries to pencak silat athletes can occur in the upper body or lower body with mild to severe levels of injury marked by further action on injuries experienced by pencak silat athletes.